Carbon Dioxide Capture through Physical and Chemical Adsorption Using Porous Carbon Materials: A Review - Oneesha H. P. Gunawardene; Chamila A. Gunathilake; Kumar Vikrant; Sumedha M. Amaraweera (Atmosphere, 2022)
Due to rapid industrialization and urban development across the globe, the emission of carbon dioxide (CO2) has been significantly increased, resulting in adverse effects on the climate and ecosystems. In this regard, carbon capture and storage (CCS) is considered to be a promising technology in reducing atmospheric CO2 concentration. Among the CO2 capture technologies, adsorption has grabbed significant attention owing to its advantageous characteristics discovered in recent years. Porous carbon-based materials have emerged as one of the most versatile CO2 adsorbents. Numerous research activities have been conducted by synthesizing carbon-based adsorbents using different precursors to investigate their performances towards CCS. Additionally, amine-functionalized carbon-based adsorbents have exhibited remarkable potential for selective capturing of CO2 in the presence of other gases and humidity conditions. The present review describes the CO2 emission sources, health, and environmental impacts of CO2 towards the human beings, options for CCS, and different CO2 separation technologies. Apart from the above, different synthesis routes of carbon-based adsorbents using various precursors have been elucidated. The CO2 adsorption selectivity, capacity, and reusability of the current and applied carbon materials have also been summarized. Furthermore, the critical factors controlling the adsorption performance (e.g., the effect of textural and functional properties) are comprehensively discussed. Finally, the current challenges and future research directions have also been summarized.